Comparison of total PM emissions emitted from electric and internal combustion engine vehicles: An experimental analysis - Woo, Sang -Hee; Jang, Hyungjoon; Lee, Seung-Bok; Lee, Seokhwan (Elsevier BV, 2022)
Electric vehicles (EVs) are regarded as zero emission vehicles due to the absence of exhaust emissions. However, they still contribute non-exhaust particulate matter (PM) emissions, generated by brake wear, tire wear, road wear, and resuspended road dust. In fact, because EVs are heavier than internal combustion engine vehicles (ICEVs), their non-exhaust emissions are like to be even higher. While total PM emissions, including exhaust and non-exhaust PM emissions, from ICEVs and EVs have been compared based on the emission factors (EFs) listed in national emission inventories, there have been no comparisons based on experimental determinations. In this study, exhaust and non-exhaust emissions generated from a gasoline ICEV, diesel ICEV, and EV were experimentally investigated. The results showed that the EFs for the total PM emissions of ICEVs and EV were dependent on the inclusion of secondary exhaust PM, the brake pad type, and the regenerative braking intensity of the EV. When only primary exhaust PM emissions were considered in vehicles equipped with non-asbestos organic (NAO) brake pads, the total PM10 EF of the EV (47.7-49.3 mg/V & BULL;km) was 10-17 % higher than those of the gasoline ICEV (42.3 mg/V & BULL;km) and diesel ICEV (43.2 mg/V & BULL;km). However, in vehicles equipped with low-metallic (LM) brake pads, the total PM10 EF of the EV (49.2-57.7 mg/V & BULL;km) was comparable or lower than those of the gasoline ICEV (56.3 mg/V & BULL;km) and diesel ICEV (57.2 mg/V & BULL;km). When secondary PM emissions were included, the EF was always significantly lower for the EV than ICEVs. The total PM10 EF of the EV (47.7-57.7 mg/V & BULL;km) was lower than those of the gasoline ICEV (56.5-70.5 mg/V & BULL;km) and diesel ICEV (58.0-72.0 mg/V & BULL;km). Since secondary PM particles are mostly of submicron size, the EFs of the PM2.5 fraction of the ICEVs (28.7-33.0 mg/V & BULL;km) were two times higher than those of the EV (13.9-17.4 mg/V & BULL;km).